Analisis Tingkat Kebisingan Aktivitas Stone Crusher Pada Tambang Indonesia Growth Project (IGP) Morowali - Dhani, Sheena Ramadhia Asmara; Sunardi, Sunardi (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2025)
The Indonesia Growth Project (IGP) Morowali is an integrated nickel mining and processing project. The mining activities are carried out at the stone crusher workshop location, which generates very high noise levels, exposing workers in the stone crusher section to noise daily. Therefore, a study is needed to analyze the noise levels to determine their intensity. This research is descriptive study.. Noise data collection was conducted over a year using a Sound Level Meter, following the method outlined in Kepmen-LH No. 48 of 1996. The highest measured noise level was an average of 95.07 dB in August, while the lowest noise level was an average of 85.07 dB in November. The noise intensity in the crusher machine area is quite high, making the use of personal protective equipment (PPE), such as earplugs, recommended for workers around the crusher machine area, considering their exposure to high noise levels during work. Keywords: noise level, stone crusher